Baroreflex activation therapy in advanced heart failure: A long‐term follow‐up - Dong Wang; Johanna Mueller‐Leisse; Henrike A.K. Hillmann; Jörg Eiringhaus; Dominik Berliner; Nizar Karfoul; Jan D. Schmitto; Arjang Ruhparwar; Johann Bauersachs; David Duncker (ESC Heart Failure)
Abstract Aims Baroreceptor activation therapy (BAT) is a promising new treatment strategy for patients with heart failure with reduced ejection fraction (HFrEF). It provides symptomatic relief, improvement in left ventricular function and reduction of cardiac biomarkers. Data regarding the long‐term effect of BAT on HFrEF are scarce. This retrospective, monocentric study aimed to assess long‐term outcome in patients who underwent BAT. Methods Patients with HFrEF who received BAT at Hannover Medical School between 2014 and 2023 were followed until the latest available follow‐up. Symptom burden, echocardiography and laboratory testing were assessed before BAT implantation and in subsequent follow‐ups. Results Twenty‐three patients (mean age 66 ± 10 years, 83% male) with HFrEF were included in the study. Aetiology of heart failure was ischaemic in 70%. The majority of patients (96%) suffered from New York Heart Association (NYHA) III with a mean left ventricular ejection fraction (LVEF) of 23 ± 8% and N‐terminal pro‐B‐type natriuretic peptide (NT‐proBNP) of 2463 ± 2922 pg/mL. A complication occurred in one patient during BAT implantation (4%). The mean follow‐up was 3 ± 2 (max. 7.5) years. BAT reduced NYHA classification in 12 patients (52%) after 1 year, of which one patient remained in ameliorated NYHA for 7.5 years. Echocardiographic evaluation revealed significant improvement in LVEF by 9 ± 9% after 1 year (P < 0.001) and by 11 ± 9% (P = 0.005) after 2 years. In addition, BAT mildly reduced NT‐proBNP in the first 2 years [non‐significantly after 1 year by 396 ± 1006 pg/mL and significantly after 2 years by 566 ± 651 pg/mL (P = 0.039)]. Seven patients reaching the recommended replacement time underwent device exchange. Four patients died during observation time. Conclusions BAT resulted in a substantial reduction in NYHA classification and improvement in LVEF that lasted over long‐term follow‐up in many patients. NT‐proBNP level decreased interim in long‐term follow‐up. These findings highlight the long‐term efficacy and potential benefits of BAT as a therapeutic intervention for patients with HFrEF.